Young people's views on the potential use of telemedicine consultations for sexual health: results of a national survey - Garrett, Cameryn C (BioMed Central, 2011)
BACKGROUND: Young people are disproportionately affected by sexually transmissible infections in Australia but face barriers to accessing sexual health services, including concerns over confidentiality and, for some, geographic remoteness. A possible innovation to increase access to services is the use of telemedicine. METHODS: Young people's (aged 16-24) pre-use views on telephone and webcam consultations for sexual health were investigated through a widely-advertised national online survey in Australia. Descriptive statistics were used to describe the study sample and chi-square, Mann-Whitney U test, or t-tests were used to assess associations. Multinomial logistic regression was used to explore the association between the three-level outcome variable (first preference in person, telephone or webcam, and demographic and behavioural variables); odds ratios and 95%CI were calculated using in person as the reference category. Free text responses were analysed thematically. RESULTS: A total of 662 people completed the questionnaire. Overall, 85% of the sample indicated they would be willing to have an in-person consultation with a doctor, 63% a telephone consultation, and 29% a webcam consultation. Men, respondents with same-sex partners, and respondents reporting three or more partners in the previous year were more willing to have a webcam consultation. Imagining they lived 20 minutes from a doctor, 83% of respondents reported that their first preference would be an in-person consultation with a doctor; if imagining they lived two hours from a doctor, 51% preferred a telephone consultation. The main objections to webcam consultations in the free text responses were privacy and security concerns relating to the possibility of the webcam consultation being recorded, saved, and potentially searchable and retrievable online. CONCLUSIONS: This study is the first we are aware of that seeks the views of young people on telemedicine and access to sexual health services. Although only 29% of respondents were willing to have a webcam consultation, such a service may benefit youth who may not otherwise access a sexual health service. The acceptability of webcam consultations may be increased if medical clinics provide clear and accessible privacy policies ensuring that consultations will not be recorded or saved.